Development of a Web-Based Service System for the Empowerment of Mandalamekar Village - Aan Kardiana; Suhaeri Suhaeri; Hilma Suyana; Arunia Salsanur Fais (SAN Scientific, 2026)
Efficient and effective public services are key indicators of successful village governance. Mandalamekar Village, Bandung Regency, faces significant challenges in its manual population administration services. These issues reduce service efficiency, data accuracy, and transparency in village administration management. This community service activity developed an integrated web-based village service system and increased the capacity of village officials through technology training. We used a Research and Development (R&D) approach with a Software Development Life Cycle (SDLC) cycle, including needs analysis, design, development, implementation, field trials, training, mentoring, and system evaluation and improvement. The implementation results showed increased service efficiency (60% reduction in time), data recording accuracy, and community satisfaction (85% of respondents were satisfied). This activity had a positive impact in terms of improving the quality of administrative services, the digital skills of village officials, and public trust in village governance.